1999
DOI: 10.1016/s0886-3350(99)00087-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous opacification after neodymium:YAG posterior capsulotomy

Abstract: The prevalence of vitreous opacification after Nd:YAG laser posterior capsulotomy was significantly higher in diabetic than in nondiabetic eyes. Viterectomy was effective for this type of opacification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The disadvantage of a smaller PCCC is the visual axis obscuration caused by the proliferation of the lens epithelial cells from the PCCC margin. [22][23][24][25] The reported incidence of visual axis obscuration with PMMA IOLs is 60% to 100% when capsulotomy is not combined with anterior vitrectomy. 26 In our study, we reported that in children younger than 5 years who underwent PCCC without anterior vitrectomy using PMMA IOLs, 62.5% developed visual axis obscuration at an average follow-up of 13.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage of a smaller PCCC is the visual axis obscuration caused by the proliferation of the lens epithelial cells from the PCCC margin. [22][23][24][25] The reported incidence of visual axis obscuration with PMMA IOLs is 60% to 100% when capsulotomy is not combined with anterior vitrectomy. 26 In our study, we reported that in children younger than 5 years who underwent PCCC without anterior vitrectomy using PMMA IOLs, 62.5% developed visual axis obscuration at an average follow-up of 13.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…It involves removal of the central part of the posterior capsule to prevent equatorial lens epithelial cell (LEC) migration and formation of PCO, and has been utilized as a primary planned procedure for the prevention of PCO formation in adults [ 15 , 16 ]. The PCCC procedure eradicates the need for Neodymium:yttrium aluminum garnet (Nd:YAG) laser capsulotomy, that is associated with numerous complications including retinal tears, IOL damage, cystoid macular edema (CME), anterior hyaloid opacity, inflammation, and increased intraocular pressure (IOP) [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this procedure is associated with a small risk of complications such as vitreous floaters, a rise in intraocular pressure, macular edema, and damage and decentration of the IOL. [38]…”
Section: Introductionmentioning
confidence: 99%